2000
DOI: 10.1042/cs1000043
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency heart rate variability: reproducibility in cardiac transplant recipients and normal subjects

Abstract: Heart rate variability is a measure of autonomic nervous influence on the heart. It has been suggested that it could be used to detect autonomic reinnervation to the transplanted heart, but the reproducibility of the measurement is unknown. In the present study, 21 cardiac transplant recipients and 21 normal subjects were recruited. Three measurements of heart rate variability were performed during the day: in the morning, in the early afternoon and in the late afternoon. These tests were then repeated 1 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 13 publications
2
41
1
Order By: Relevance
“…However, additional studies are necessary to determine if these findings are demonstrable in subjects with diseases that cause disturbances of the autonomic nervous system. Unlike other studies (22,27), our results indicate that intra-individual measurements can show good reproducibility, even for short-time recordings in the supine position if external factors that alter autonomic balance are well controlled. Thus, studies questioning reproducibility use different ECG recording sequences.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, additional studies are necessary to determine if these findings are demonstrable in subjects with diseases that cause disturbances of the autonomic nervous system. Unlike other studies (22,27), our results indicate that intra-individual measurements can show good reproducibility, even for short-time recordings in the supine position if external factors that alter autonomic balance are well controlled. Thus, studies questioning reproducibility use different ECG recording sequences.…”
Section: Discussionmentioning
confidence: 64%
“…Since it is a noninvasive and inexpensive method, several recordings can be easily obtained as a function of time in the same individual to evaluate the efficacy of therapeutic interventions. Therefore, some studies have been specifically designed to evaluate the reproducibility of the measurements since autonomic balance is subjected to a large number of central and peripheral control systems, all of them potentially affecting HR control (17)(18)(19)(20)(21)(22)25). Some studies have shown good reproducibility in HRV analysis (17,20,21), while others have reported the opposite (22,27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations